PROCESS AUTOMATION THROUGH PD PROVIDER IMPROVEMENT (Journal of Science-Innovative Research in Uzbekistan, 2024)
Currently, the PD feeder is mainly installed on gin, 1-XK, SCH- 02 equipment. The main function of this equipment is to pick and supply seeded cotton. The process is automated by improving the integral parts of the PD provider.